MENGURAI BENANG KUSUT BIROKRASI DIGITAL: SYSTEMATIC LITERATURE REVIEW TERHADAP HAMBATAN MANAJERIAL DALAM IMPLEMENTASI E-GOVERNMENT - Lingga Baskoro, Kukuh; Sunara Akbar, Rasona; Anung Prabadhi, Isidorus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of e-government in Indonesia frequently encounters significant effectiveness challenges despite the continous rise in application innovation. This study aims to identify and analyze the managerial, policy, and socio-technical barriers that trigger the ineffectiveness of government information systems through a systematic literature review. Utilizing the PRISMA (Preferre Reporting Items for Systematic Review and Meta-Analyses) method, 30 selected studies from Google Scholar, Crossref, and Semantic Scholar databases were analyzed in depth. The findings indicate that the failure of information system implementation within government environments is predominantly driven by managerial factors rather than technical software issues. Three main themes were identified: first, bureaucratic fragmentation and sectoral ego hindering data integration. Second, socio-technical resistance and the digital divide, particularly among the elderly. Third, weak human resource governance and a lack of incentives for grassroots implementers. This study concludes that a pradigm shift is required from apllication-oriented strtegies toward thoe focused on change management and user inclusion. Policy recommendations include the development of cross-institutional integration SOPs, strengthening responsive helpdesk, and implementing user-friendly interface designs for all community gropus.